Analisis Perbandingan Kinerja Keuangan Perusahaan Sebelum dan Sesudah Akuisisi Yang Listing di Indeks Saham Syariah (ISSI) - Ningsih, Setia; Rahman, Supandi (Scimadly Publishing, 2022)
This study aims to determine the differences in the company's financial performance between before and after the acquisition of companies listed in ISSI which are proxied by financial ratios Current Ratio (CR), Net Profit Margin (NPM), Total Assets Turnover (TATO), Debt to Equity Ratio. (DER), Return On Assets (ROA), Return On Equity (ROE), Earnings Per share (EPS). The research period used is 2016-2020. The population in this study includes all companies registered with ISSI that carried out acquisition activities in 2018 totaling 74 companies. The sample selection technique used the Purposie Sampling method and obtained 7 companies. Data analysis methods used in this research include normality test, and paired sample t-test. The normality test is used to see whether the data is normally distributed or not, if the data is normally distributed then the paired sample t-test is used, but if the data is not normally distributed, the Wilcoxon signed ranks test is used. The data analysis method used in this study is the Paired sample t-test.The results of this study indicate that all research variables are Current Ratio (CR), Net Profit Margin (NPM), Total Assets Turnover (TATO), Debt to Equity Ratio (DER), Return On Assets (ROA), Return On Equity (ROE). ), Earnings Per share (EPS) did not experience a significant change after the acquisition.